2016
DOI: 10.1136/bmjopen-2015-009870
|View full text |Cite
|
Sign up to set email alerts
|

Association between toothbrushing and risk factors for cardiovascular disease: a large-scale, cross-sectional Japanese study

Abstract: ObjectivesTo clarify the association between toothbrushing and risk factors for cardiovascular disease—namely, hypertension (HT), diabetes mellitus (DM), dyslipidaemia (DL), hyperuricaemia (HUA) and chronic kidney disease (CKD).DesignA large-scale, single-centre, cross-sectional study.SettingSt Luke's International Hospital, Center for Preventive Medicine, Tokyo, Japan, between January 2004 and June 2010.ParticipantsThis study examined the toothbrushing practices of 85 866 individuals according to the 3-catego… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
48
3
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 37 publications
(58 citation statements)
references
References 18 publications
3
48
3
4
Order By: Relevance
“…After retrieving full‐text of the remaining 179 articles, 32 articles were excluded because of insufficient data to calculate the risk estimates, and 127 were excluded as tooth brushing was not a risk factor. Eventually, we included 20 studies in this meta‐analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After retrieving full‐text of the remaining 179 articles, 32 articles were excluded because of insufficient data to calculate the risk estimates, and 127 were excluded as tooth brushing was not a risk factor. Eventually, we included 20 studies in this meta‐analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Tooth brushing is considered as a fundamental self‐care behaviour for the maintenance of oral health. Some studies have suggested that tooth brushing was associated with many health problems, including gingivitis, dental caries, tooth decay, periodontal disease, head and neck cancer, dyslipidemia, and endothelial dysfunction . …”
Section: Introductionmentioning
confidence: 99%
“…This study population was considered as an ‘apparently healthy population’ since they came to the center by themselves to have annual regular health checkup without specific complaints, and also provided a general history of comorbidities. We have previously published studies using this database (17, 18, 19, 20, 21, 22, 23). The study subjects were similar to our previous studies, but this study design, inclusion and exclusion criteria, and outcomes were different from our previous studies.…”
Section: Methodsmentioning
confidence: 99%
“…Toothbrushing is the most commonly used oral hygiene procedure. Recent studies reported that a low frequency of toothbrushing was associated with a high level of risk for cardiovascular disease (de Oliveira, Watt, & Hamer, ) and diabetes mellitus (Kuwabara et al., ). Thus, toothbrushing has a potential link to MetS, which is a precursor of cardiovascular disease and diabetes mellitus.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies reported that a low frequency of toothbrushing was associated with a high level of risk for cardiovascular disease (de Oliveira, Watt, & Hamer, 2010) and diabetes mellitus (Kuwabara et al, 2016).…”
mentioning
confidence: 99%